Endovascular repair for abdominal aortic aneurysms. Issue 22 (4th March 2021) - Debono, Samuel; Nash, Jennifer; Tambyraja, Andrew L; Newby, David E; Forsythe, Rachael O
Abstract : Management of abdominal aortic aneurysms has been the subject of rigorous scientific scrutiny. Prevalence studies have directed the formation of screening programmes, and observational studies and randomised controlled trials have defined aneurysm growth and treatment thresholds. Pre-emptive intervention with traditional open surgical repair has been the bedrock of improving long-term outcome and survival in patients with abdominal aortic aneurysms but it is associated with a significant procedural morbidity and mortality. Endovascular aneurysm repair (EVAR) has substantially reduced these early complications and has been associated with promising results in both elective and emergency aneurysm repair. However, the technique has brought its own unique complications, endoleaks. An endoleak is the presence of blood flow within the aneurysm sac but outside the EVAR graft. Although in randomised control trials EVAR was associated with a reduced early mortality compared with open repair, its longer-term morbidity and mortality was higher because endoleak development is associated with a higher risk of rupture. These endoleak complications have necessitated the development of postoperative imaging surveillance and re-intervention. These contrasting benefits and risks inform the selection of the mode of repair and are heavily influenced by individual patient factors. An improved strategy to predict endoleak development could further help direct treatment choice for patients and improve both early and late outcomes. This article reviews current EVAR practice, recent updates in clinical practice guidelines and the potential future developments to facilitate the selection of mode of aneurysm repair. Trial registration number: ClinicalTrials.gov NCT04577716 .